Innovation in agriculture reduces pressure on forests - Sonwa, D.J.; Hanna, R. (Center for Tropical Research/University of California, Los Angeles, 2017)
Population growth and the expansion of small holders and industrial and large scale agriculture are considered to be major drivers of deforestation and forest degradation in the Congo Basin. Various innovations in agricultural practices are necessary to improve productivity, enhance producer livelihoods and reduce conversion of forests into fields for agriculture. These innovations can include improved crop varieties and crop production and protection practices, as well as post-harvest handling and better facilities to market small farmer products.